2015 International Conference on Intelligent Information Hiding and Multimedia Signal Processing (IIH-MSP) 2015
DOI: 10.1109/iih-msp.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

An Imperceptible Information Hiding in Encoded Bits of Speech Signal

Abstract: This paper presents an imperceptible information hiding approach applied to the G.723.1 low-bit-rate codec, which is already being used extensively in Voice-over-Internet Protocol. We show that the encoded bits of the stochastic excitation pulse parameters are more suitable for data embedding than the encoded bits of other speech parameters. We also propose a voice-activity detection method that uses the residual signal energy of the speech signal to increase the data embedding capacity. The results of an impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Wu et al [8] used the differential signal-to-noise ratio (DSNR) to evaluate the noise tolerance of G.729 encoder parameters, and selected the least significant bits to embed secret information by using the cross-coding technique. Lin [9] analyzed the parameter bits of the G.723.1 encoder and concluded that bits of the random excitation pulse parameters are more suitable for data embedding than other parameter bits. Huang et al [10] used the least significant bits (LSB) matching algorithm that utilizes random sequences as embedding criteria to achieve secure communications with better performance.…”
Section: Related Workmentioning
confidence: 99%
“…Wu et al [8] used the differential signal-to-noise ratio (DSNR) to evaluate the noise tolerance of G.729 encoder parameters, and selected the least significant bits to embed secret information by using the cross-coding technique. Lin [9] analyzed the parameter bits of the G.723.1 encoder and concluded that bits of the random excitation pulse parameters are more suitable for data embedding than other parameter bits. Huang et al [10] used the least significant bits (LSB) matching algorithm that utilizes random sequences as embedding criteria to achieve secure communications with better performance.…”
Section: Related Workmentioning
confidence: 99%